Inhibition of interleukin 6 signalling and renal function: A Mendelian randomization study. Issue 7 (10th February 2021) - Ryan, David K.; Karhunen, Ville; Walker, Drew J.; Gill, Dipender
Abstract : Inhibition of interleukin 6 (IL‐6) signalling has been proposed as a potential cardioprotective strategy for patients with chronic kidney disease (CKD), but the direct effects of IL‐6 inhibition on renal function are not known. A Mendelian randomization (MR) study was performed to investigate the association of genetically proxied inhibition of IL‐6 signalling with estimated glomerular filtration rate (eGFR), CKD and blood urea nitrogen (BUN). Inverse‐variance weighted MR was used as the main analysis, with sensitivity analyses performed using simple median, weighted median and MR‐Egger methods. There was no evidence for an association of genetically proxied inhibition of IL‐6 signalling (scaled per standard deviation unit decrease in C‐reactive protein) with log eGFR (0.001, 95% confidence interval −0.004‐0.007), BUN (0.009, 95% confidence interval −0.003‐0.021) and CKD (odds ratio 0.948, 95% confidence interval 0.822‐1.094). These findings do not raise concerns for IL‐6 signalling having large adverse effects on renal function.